1997
DOI: 10.1021/ie970458i
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Removal from Aqueous Solutions by Chelation in Supercritical Carbon Dioxide Using Fluorinated β-Diketones

Abstract: Copper removal from aqueous solutions by chelation in supercritical carbon dioxide was investigated. The chelating agents were 1,1,1-trifluoroacetylacetone (TFA) and 2,2-dimethyl- 6,6,7,7,8,8,. Extraction efficiencies were determined for a single equilibrium stage in the temperature range 308-328 K and the pressure range 9.9-24.0 MPa and ranged from 4% to 84%. The extraction efficiencies increased with increasing the initial amount of chelating agent and with decreasing the initial copper concentration. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…When metal ions are chelated with suitable organic ligands, their solubility can be significantly increased. Some highly CO 2 -philic fluorinated or siloxane-based ligands are in removing various metals from solid and liquid matrices [176][177][178][179]. Zhang et al [123] have developed an extraction method using RAFT polymerization in order to functionalize a bipyridine group with VAc oligomers.…”
Section: Co 2 -Philic Polymers and Surfactantsmentioning
confidence: 99%
“…When metal ions are chelated with suitable organic ligands, their solubility can be significantly increased. Some highly CO 2 -philic fluorinated or siloxane-based ligands are in removing various metals from solid and liquid matrices [176][177][178][179]. Zhang et al [123] have developed an extraction method using RAFT polymerization in order to functionalize a bipyridine group with VAc oligomers.…”
Section: Co 2 -Philic Polymers and Surfactantsmentioning
confidence: 99%
“…Upon varying the temperature and pressure, the solubility of the copper ions in SCCO 2 was improved significantly and the extraction efficiency of copper ions was increased from 4% to 84%, respectively [36,37]. Similarly, Cui et al observed successful extraction of Cu 2+ ions from the silica surface using benzylacetone as chelating agent in supercritical CO 2 [38].…”
Section: Xps Studymentioning
confidence: 96%
“…For complexes with the same ligand, as oxidation state of the metal atom increases, the MP becomes more soluble. Using ligands with higher solubility, such as fluorinated ligands or addition of a modifier may be beneficial to increase solubility of the precursors (Murphy and Erkey, 1997;Aggarwal et al, 2013).…”
Section: Supercritical Depositionmentioning
confidence: 99%